Análise do impacto da previdência rural sobre as áreas rurais do Brasil - Zague, Arthur Sardeiro (2018)
The main objective of this study is to evaluate the impact of rural pensions on the reduction of poverty in rural areas of Brazil in the period from 2004 to 2015. Currently, more than 70% of total benefits issued by the Social Security Rural are pensions worth 1 minimum wage. This benefit corresponds to the pension received by the special insured persons, whose access to the benefit is granted by proving the exercise of rural activity. Special insured persons are rural workers who carry out their activities under the family economy regime. In order to carry out the present study, the influence of income growth and inequality reduction on poverty reduction was verified. After this initial analysis, the per capita household income (RDPC) of the rural households analyzed was broken down into 8 income sources. Then, the role of each source of income in income growth and in reducing inequality was verified, with a priority focus on the source of income related to special insured pensions. The analyzes were conducted for two groups: rural households in general and households with at least one special insured beneficiary of retirement. The results indicated that income growth had a decisive impact on the poverty reduction of the two groups analyzed. For rural households in general, at least 79.3% of poverty reduction was driven by the growth of the RDPC. Similar situation was observed for the group containing only households with at least one special insured beneficiary of retirement, where it was verified that the contribution of the growth of the RDPC was at least 73.7%. Decomposition and analysis of the RDPC revealed that for rural households as a whole, special insured pensions accounted for approximately 29% of RDPC growth in the period under analysis. For households with special insured beneficiaries of pensions, this source of income accounted for an even greater percentage of this growth, around 65%. The analysis of the impact of income sources on the reduction of inequality revealed a small contribution of the benefit of the special insured to the reduction of inequality in the rural households as a whole, so that around 4% of the reduction in the observed Gini index is associated with this portion of income. For households with special insured persons benefiting from pensions, the participation of the social security benefit in the reduction of the Gini index was substantially higher, approximately 54%. Thus, the presented results show that there is evidence of the performance of the social security benefit received by the special insured on the poverty reduction of the two analyzed groups.